(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Isolation is done for proper control of moisture, good accessibility and visibility, to provide adequate space for instrumentation and operation. Most of the children are non-cooperative during treatment. So, isolation is mandatorily necessary for pediatric patients. Studies have shown that there are successful retention rates of adhesive restoration when a rubber dam is used rather than any other isolation technique. The judicious use of rubber dam ensures greater patient comfort and delivery of high-quality dental care to pediatric patients.